Government and business in the Caribbean: in search of the right relationship - Palmer, Ransford W. ([s.n.] [S.l.], 1993)
Looks at the importance and limitation of government; government as protector of inefficiency; government as a promoter of efficiency; lessons from Korea; and, government and business as a team.